2017
DOI: 10.3847/1538-4357/aa8d17
|View full text |Cite
|
Sign up to set email alerts
|

Halo Intrinsic Alignment: Dependence on Mass, Formation Time, and Environment

Abstract: In this paper we use high-resolution cosmological simulations to study halo intrinsic alignment and its dependence on mass, formation time and large-scale environment. In agreement with previous studies using N-body simulations, it is found that massive halos have stronger alignment. For the first time, we find that for given halo mass, older halos have stronger alignment and halos in cluster regions also have stronger alignment than those in filament. To model these dependencies we extend the linear alignment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
5
28
2
Order By: Relevance
“…Investigating the dependence of the strength of the tidally induced shape alignments on M, R f , and the type of the cosmic web, it has been found that the more massive galactic halos yield strongerû 3 -ê alignments (û 1 -ê anti-alignments) and that the increment of R f weakens the alignment tendency (see Figures 4). These numerical results are consistent with what the previous works already found (Joachimi et al 2013;Zhang et al 2013;Chen et al 2016;Hilbert et al 2017;Xia et al 2017;Piras et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Investigating the dependence of the strength of the tidally induced shape alignments on M, R f , and the type of the cosmic web, it has been found that the more massive galactic halos yield strongerû 3 -ê alignments (û 1 -ê anti-alignments) and that the increment of R f weakens the alignment tendency (see Figures 4). These numerical results are consistent with what the previous works already found (Joachimi et al 2013;Zhang et al 2013;Chen et al 2016;Hilbert et al 2017;Xia et al 2017;Piras et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Figure 4 shows quantitatively how the increment of R f weakens the shape alignments. Although the alignment tendency becomes weaker as R f increases, the shape vector,ê, still shows significant alignment (antialignment) withû 3 (û 1 ) even for the case of R f = 30 h −1 Mpc, which is consistent with the findings of the previous works (e.g., Xia et al 2017).…”
Section: Numerical Testssupporting
confidence: 92%
See 1 more Smart Citation
“…y4,0(k) − 8 21 y2,0(k) + 4 15 y0,0(k). After applying the orthogonality condition of y m , the two components of the II correlation function, ξ±(r), are given as (see Xia et al 2017, for an similar expression for the monopole moment)…”
Section: Correlationmentioning
confidence: 99%
“…The intrinsic alignment (IA) of galaxy images (Heavens et al 2000;Croft & Metzler 2000;Lee & Pen 2000;Catelan et al 2001;Crittenden et al 2001;Hirata & Seljak 2004) (See Troxel & Ishak 2015;Joachimi et al 2015;Kirk et al 2015;Kiessling et al 2015, for reviews) is known to contaminate cosmological parameter estimations from weak lensing surveys, by 5 − 10% (Mandelbaum et al 2006;Hirata et al 2007;Joachimi et al 2011;Singh et al 2015). Precise modeling of the intrinsic alignments (IAs) is thus crucial for the cosmic shear to be a useful cosmological tool (Jing 2002;Smith & Watts 2005;Bridle & King 2007;Zhang 2010;Schneider & Bridle 2010;Blazek et al 2011Blazek et al , 2015Xia et al 2017;Codis et al 2018;Yao et al 2019b,a;Vlah et al 2019;Blazek et al 2019;). On the other hand, less focus has been drawn to the cosmological information IAs encode.…”
Section: Introductionmentioning
confidence: 99%